2018
DOI: 10.1186/s12889-018-5560-0
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a cluster randomized controlled trial to study the effectiveness of an obesity and diabetes intervention (PASOS) in an immigrant farmworker population

Abstract: BackgroundStudies have shown that the prevalence of overweight, obesity and diabetes are higher in the largely Hispanic, immigrant farmworker population in California. Though to date, few interventional studies have focused on these issues in this at-risk population. The objective of this paper is to describe the study design of a cluster randomized controlled trial aimed at evaluating the effectiveness of an obesity and diabetes work place intervention in an immigrant farm worker population.MethodsPASOS is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…From these searches, initially 21 studies were identified as eligible; however, 11 studies were subsequently excluded at the data‐extraction phase for various reasons: The efficacy trials for the PEACH QLD study and the Active‐For‐Life study reported within‐group improvement—but no between‐group difference—on measures of weight status between the trial arms postintervention; Action Schools! BC, TXT2BFiT, and the YOG‐Obesity studies found no significant difference on a measure of weight status in the pre–scale‐up RCT; Camp NERF had no available data for the pre–scale‐up RCT; CHAT and PASOS had no follow‐up outcome data (authors of these studies were contacted; however, no follow‐up data were able to be supplied); the original pre–scale‐up trial of EPODE was a non‐RCT design; Healthy and Vital did not include a measure of weight status, physical activity, or nutrition as its primary outcome measure; and finally, SHED‐IT tested an additional component in the larger trial where both control and intervention arms received SHED‐IT while the intervention arm also received a weight loss maintenance programme.…”
Section: Resultsmentioning
confidence: 99%
“…From these searches, initially 21 studies were identified as eligible; however, 11 studies were subsequently excluded at the data‐extraction phase for various reasons: The efficacy trials for the PEACH QLD study and the Active‐For‐Life study reported within‐group improvement—but no between‐group difference—on measures of weight status between the trial arms postintervention; Action Schools! BC, TXT2BFiT, and the YOG‐Obesity studies found no significant difference on a measure of weight status in the pre–scale‐up RCT; Camp NERF had no available data for the pre–scale‐up RCT; CHAT and PASOS had no follow‐up outcome data (authors of these studies were contacted; however, no follow‐up data were able to be supplied); the original pre–scale‐up trial of EPODE was a non‐RCT design; Healthy and Vital did not include a measure of weight status, physical activity, or nutrition as its primary outcome measure; and finally, SHED‐IT tested an additional component in the larger trial where both control and intervention arms received SHED‐IT while the intervention arm also received a weight loss maintenance programme.…”
Section: Resultsmentioning
confidence: 99%
“…Outra variável que apresentou significância foi a escolaridade, sendo verificado nos participantes que estudaram até o ensino fundamental e nos analfabetos uma frequência alta, o que corrobora com outros estudos (17,19) . Pessoas com baixa escolaridade têm prevalência duas vezes maior para DM (25) . Desta forma, compreende-se que a educação tem influência significativa no bem-estar, tanto individual quanto coletivo (26) , ao passo que, quanto menor o nível de escolaridade, maior a prevalência de DM (23) , pois a escolaridade influenciará diretamente nas escolhas sobre promoção da saúde e prevenção de doenças (25) .…”
Section: Resultsunclassified
“…Pessoas com baixa escolaridade têm prevalência duas vezes maior para DM (25) . Desta forma, compreende-se que a educação tem influência significativa no bem-estar, tanto individual quanto coletivo (26) , ao passo que, quanto menor o nível de escolaridade, maior a prevalência de DM (23) , pois a escolaridade influenciará diretamente nas escolhas sobre promoção da saúde e prevenção de doenças (25) .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…We identi ed 21 studies that used any kind of ADPP (in 12 studies, it was the main focus [17][18][19][20][21][22][23][24][25][26][27][28] [31] were also used as a curriculum base for some of the included studies (e.g., NDEP [32] and NDPP [28]). The included studies (n = 21) targeted mostly migrants (n = 9) and ethnic groups (n = 6).…”
Section: Adapted Diabetes Prevention Programsmentioning
confidence: 99%